Variations on Transport for a Quantum Flute - Kristinn Torfason 1984- (Computer Physics Communications, 2013)
A thesis submitted in partial fulfilment of the requirements for the joint degree of Doctor of Philosophy in Physics at University of Iceland and Reykjavík University. Advisors: Andrei Manolescu (Reykjavik University), Viðar Guðmundsson (University of Iceland). A time-dependent Lippmann-Schwinger scattering model is used to study the transport of a time-modulated double quantum point contact system in the presence of perpendicular magnetic field. The conductance through the system is calculated using the Landauer-Büttiker framework. An observed magnetic field induced Fano resonance is seen in the conductance. A Generalized Master Equation (GME) is then used to describe the non-equilibrium time-dependent transport through a similar system, a short quantum wire connected to semi-infinite leads. A lattice model is used to described the leads and system, with the Coulomb interaction between the electrons in the sample included via the exact diagonalization method. The contact coupling strength between the leads and the wire is modulated by out-of-phase time-dependent potentials that simulate a turnstile device. The placement of one of the leads is fixed while the position of the other is varied. The propagation of both sinusoidal and rectangular pulses is examined. The current profiles in both leads are found to depend on not only the shape of the pulses, but also the position of the contacts. The current reflects standing waves created by the contact potentials, like in a wind musical instrument (for example, a flute). Finally thermoelectric currents through a quantum dot are studied in both the transient and steady-state regime using the GME. The two semi-infinite leads are kept at the same chemical potential but at different temperatures to produce a thermoelectric current, which has a varying sign depending on the chemical potential. A saw-tooth like profile is observed in the current along with plateaus of zero current. Tímaháð Lippmann-Schwinger líkan er notað til að rannsaka flutning rafeinda í tvöfaldri ...